2002
DOI: 10.1007/s001980200007
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Bone Turnover in Cystic Fibrosis Adults

Abstract: Cystic fibrosis (CF) patients often have low bone mineral density (BMD) and may suffer from fractures and kyphosis. The pathogenesis of low BMD in CF is multifactorial. To study bone metabolism, we collected fasting serum and urine from 50 clinically stable CF adults (mean age 28 years) and 53 matched controls to measure markers of bone formation and bone resorption. The CF subjects had moderate lung disease (FEV1: 46.1 +/- 18.6% predicted) and malnutrition (BMI: 20.0 +/- 3.3 kg/m2). Only 3 subjects had normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 19 publications
5
32
1
3
Order By: Relevance
“…A longitudinal study of BMD in CF patients concluded that both reduced bone accretion and accelerated bone loss contribute to the reduced BMD [8]. Elevated levels of bone turnover markers, including serum osteocalcin, urinary N-telopeptide and bonespecific alkaline phosphatase, have been reported in CF patients [5,6,9,10], and it has been suggested that, in CF, there is an imbalance between bone formation and bone resorption in favour of resorption [11,12]. An association between reduced 25-hydroxyvitamin D levels and reduced BMD has been reported in CF patients [7].…”
mentioning
confidence: 99%
“…A longitudinal study of BMD in CF patients concluded that both reduced bone accretion and accelerated bone loss contribute to the reduced BMD [8]. Elevated levels of bone turnover markers, including serum osteocalcin, urinary N-telopeptide and bonespecific alkaline phosphatase, have been reported in CF patients [5,6,9,10], and it has been suggested that, in CF, there is an imbalance between bone formation and bone resorption in favour of resorption [11,12]. An association between reduced 25-hydroxyvitamin D levels and reduced BMD has been reported in CF patients [7].…”
mentioning
confidence: 99%
“…Было определено значительное изменение костного обмена -повы шение процессов резорбции при малой трансформа ции со стороны формирования костной ткани, что отражалось в выраженном увеличении β CrossLaps и нормальных или несколько сниженных показате лях остеокальцина. Схожие результаты были получе ны в других исследованиях у больных МВ [3,[7][8][9][10][11]. Это свидетельствует о дисбалансе и асимметричнос ти костного обмена с превалированием костной ре зорбции.…”
Section: Discussionunclassified
“…A single study reported increasing levels of 25(OH)D post-lung transplant [ 47 ] . A lung transplant removes the effect of chronic infection and in fl ammation, though it does not change the pancreatic insuf fi ciency status or in fl uence of CFTR on other cellular function.…”
Section: Effect Of Lung Transplantationmentioning
confidence: 97%
“…Neither of these studies used matched controls. PTH is frequently observed to be higher than reference ranges, though it has not been associated with BMD in any study to date [ 12,15,23,26,43,[47][48][49][50][51][52] . Many of these studies are limited by the fact that they used local reference ranges to determine whether PTH results are normal.…”
Section: Vitamin D Levels In People With Cfmentioning
confidence: 99%